The identity, origin and impact of a 'new' buzzard species breeding in South Africa - Gwynn, Lisle (Percy FitzPatrick Institute of African Ornithology, 2015)
South Africa is traditionally known to play host to two taxa of small Buteo, the endemic and uncommon Forest Buzzard B. trizonatus, and Steppe Buzzard B. b. vulpinus, an abundant Palearctic migrant. Since the late 1970s and early 1980s, a number of buzzards appearing unlike B. trizonatus have been found breeding in the south-west Cape, particularly on the Cape Peninsula and in and around the Elgin Valley, ca.60km east of Cape Town. Some of these buzzards resemble B. b. vulpinus, whilst others appear atypical of both B. trizonatus and B. b. vulpinus. This study conducted genetic and morphological analyses on a number of buzzards sampled in the south-west Cape, and compared them with three candidate taxa considered most likely to, in full or in part, explain the identity of these ‘mystery’ buzzards. The candidate taxa were: Steppe Buzzard B. b. vulpinus, Ménétries’s Buzzard B. b. menetriesi and Forest Buzzard B. trizonatus. Morphology data and genetic samples were collected from 23 buzzards through capture with a Bal-Chatri trap, from chicks in nests, from captive birds brought to rehabilitation centres or from birds found dead. The comparative morphology of the buzzards sampled in the Cape was determined by constructing a Discriminant Component Analysis using 9 morphometric characters which had previously been established as being important in the separation of Old World Buteo taxa (Kruckenhauser et al., 2004). Blood samples were then analysed using 18 polymorphic microsatellite loci designed for Buteo swainsoni (Hull et al., 2007), using the program STRUCTURE 2.3 to analyse the population assignment of the sampled buzzards. The majority of buzzards were found to most closely match B. trizonatus or B. b. vulpinus in their morphology (52%), and their genetic signature (65%). Additionally, two unidentified genetic signatures were evident. One of these signatures remains unresolved, because buzzards with this genetic signature lacked morphological data. The second signature, however, was displayed by buzzards with larger morphology than is known from both B. b. vulpinus and B. trizonatus. Based on previous research these larger buzzards lay most closely within the morphospace of B. b. menetriesi, being far removed from the morphospace of both B. b. vulpinus and B. trizonatus. Thus, it is conceivable that some of the birds belong to this taxon.